Penanganan Anak Autis Dengan Terapi Okupasi Pada Anak Kelompok B di Pra TK-TK Lazuardi Kamila Global Islamic School Surakarta Tahun Ajaran 2015/2016 - Sugiarti, Ratna; , Dra. Surtikanti, S.H., M.Pd (2016)
Children with autism need to be given special treatment appropiate that the child can behave like normal children. This study aims to determine the treatment for autism children with occupational therapy. This study is a qualitative descriptive approach. This study was conducted in April 2016 in Kindergarten Lazuardi Kamila Global Islamic School to the subject an autistic child in group B. Data collection techniques in this study using observation , interviews and documentation. Analysis of the data in this study using the analysis model of Miles and Huberman, is to perform data reduction, presentation of data (data display ), and conclusion drawing. Results of research on the treatment of children with autism with this occupational therapy activities provided include throwing activities and catch the ball , lifting the ball with both hands and feet on tiptoe , walk on the plank , jump using one and two feet. This activity can improve skills strengthen muscles in your arms and fingers so that the child can hold objects , writing, drawing , coloring and self-help activities such as bathing, dressing, eating, wearing shoes.